The PB2-E627K Mutation Attenuates Viruses Containing the 2009 H1N1 Influenza Pandemic Polymerase - Jagger, Brett W. (American Society of Microbiology, 2010)
The swine-origin H1N1 influenza A virus emerged in early 2009 and caused the first influenza pandemic in 41 years. The virus has spread efficiently to both the Northern and the Southern Hemispheres and has been associated with over 16,000 deaths. Given the virus’s recent zoonotic origin, there is concern that the virus could acquire signature mutations associated with the enhanced pathogenicity of previous pandemic viruses or H5N1 viruses with pandemic potential. We tested the hypothesis that mutations in the polymerase PB2 gene at residues 627 and 701 would enhance virulence but found that influenza viruses containing these mutations in the context of the pandemic virus polymerase complex are attenuated in cell culture and mice.